Sustainability economics: General versus specific, and conceptual versus practical - Baumgärtner, Stefan; Quaas, Martin F. (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
We clarify the definition and interpretation of “sustainability economics” (Baumgärtner and Quaas 2010) in response to recent comments by van den Bergh (2010), Bartelmus (2010) and others. For that sake, we distinguish between general and specific definitions of sustainability and sustainability economics, as well as between conceptual and practical approaches.
Keywords: Economic; Environmental Accounting; Sustainability; 330 Wirtschaft